Studying the effect of concentration factors on the process of chemical metallization of powdered polyvinylchloride - Moravskyi, Volodymyr; Kucherenko, Anastasiia; Kuznetsova, Marta; Dziaman, Iryna; Grytsenko, Oleksandr; Dulebova, Ludmila (Eastern-European Journal of Enterprise Technologies, 2018)
Influence of concentration of components of chemical metallization solutions on the process of copper reduction on activated polyvinylchloride surface has been studied. It has been established that changes in concentrations of copper sulfate, trilon B and formaldehyde can effectively influence the metallization process. It was shown that the loss of stability of chemical metallization solutions and formation of colloidal solutions makes it is impossible to obtain a metallized polymeric material since copper reduction occurs in the solution volume. Copper reduction in the solution volume occurs because of presence of insoluble colloidal particles of copper hydroxide which are centers of nucleation of copper reduction. At such centers, copper reduction occurs as a result of reaction with formaldehyde and is accompanied by high volumes of hydrogen evolvement. It has been established that the formation of copper coating on an activated polymer surface occurs only with the use of true chemical metallization solutions. The main factor determining stability of chemical metallization solutions is complexing. It was shown that trilon B concentration under 40 mmol/l is not sufficient to bind all Cu2+ ions in a complex which prevents formation of insoluble copper hydroxide in an alkaline medium. The growth of trilon B concentration above 53 mmol/l results in reduction of a portion of copper in a form of hydroxide and formation of true solutions. It has been established that concentration of copper sulfate and alkali exerts the main influence on the mechanism of copper reduction in the case of true solutions. The growth of pH of chemical metallization solutions above 12 brings about an increase in the portion of copper that is reduced by the exchange reaction with zinc.